Evaluation of key genes and biological pathways that play a role in primary Sjogren syndrome by using a systems biology approach - Validad, Hanieh; Parvaie, Parvin; Nomiri, Samira; Miriâ€Moghaddam, Ebrahim; Safarpour, Hossein (Iranian Journal of Pharmaceutical Sciences, 2023)
Primary Sjogren syndrome (PSS) is one of the most common systemic autoimmune diseases. Lymphocytic infiltration of exocrine glands, especially lacrimal and salivary in PSS, causes ocular and oral dryness. Dry mouth may lead to difficulty in speaking, chewing, and swallowing and result in reduced quality. The pathogenesis of PSS involves multiple factors, such as genetic, environmental, and immunological factors. Despite extensive research over the last few decades, the exact etiology and progression of PSS and its inflammatory lesions is still unknown. Gene co-expression network analysis (WGCNA) is a system biology method that can be used to describe the correlation between different genes and find modules of highly correlated genes and key genes. Also, by using these modules, we can get gene ontology information and biological pathways. In this study, we used WGCNA to analyze the GSE40611 dataset, which consists of 17 PSS patients and 18 healthy controls. We construct a co-expression network for mRNA expression data of patients and control groups and then find the most significant module and hub genes that play important roles in PSS. We also identify biological pathways and related miRNA for hub genes. Among all the modules, turquoise had the most correlation with PSS and some of the hub genes, including GPR18, FCRL1, VNN2 and etc. Also, a large number of pathways were identified in the turquoise module, most of them related to immune system activity, like T-cell activation, lymphocyte differentiation, leukocyte and lymphocyte activation, regulation of immune system processes, regulation of immune response, and cell-cell adhesion. External validation using bulk RNA sequencing data also confirmed the presence of selected hub-genes in pathogenicity of PSS. Finally, these results can lead to finding key players in treatment of PSS.